Improving Teacher's Ability through Training in Learning Strategies Based on Cooperative STAD Techniques - Triasianingrum Afrikani; Etin Solihatin; Diana Nomida Musnir (STKIP Singkawang, 2020)
This research aims to improve the ability of teachers through cooperative learning strategies based on STAD techniques in grades VII, VIII, and IX at Junior High School 8 Bogor. This study using the method of action research. The model chosen in this action research is Lewin's cycle model in Mills which has the view that action research is depicted as a spiral cycle and includes stages: (a) planning (plan), (b) action (act), (c) observation, and (d) reflection and revision of action plans in the cycle if they are still needed for improvement. The results showed that 1) The application of the STAD cooperative learning strategies through training proved to contribute to the second cycle and the third cycle on improving the ability of teachers to design lesson plans; 2) Implementation of learning with cooperative learning strategies STAD techniques, the exploration of teachers provides information with learning media to be analyzed by students, the elaboration of the teacher guides the discussion where each group has a peer tutor and motivates each group to do cooperative skills; 3) The implementation of STAD techniques of cooperative learning techniques through training in the implementation of preliminary learning activities contribute to the second cycle in the third cycle on improving the ability of teachers to carry out preliminary learning activities. The STAD strategy can increase the ability of teachers.